High pressure processing of food-grade emulsion systems: Antimicrobial activity, and effect on the physicochemical properties. (February 2019) - Gharibzahedi, Seyed Mohammad Taghi; Hernández-Ortega, César; Welti-Chanes, Jorge; Putnik, Predrag; Barba, Francisco J.; Mallikarjunan, Kumar; Escobedo-Avellaneda, Zamantha; Roohinejad, Shahin
Abstract: The use of high pressure processing (HPP) for development of stable emulsion-based delivery systems has been recently increased. Under adequate conditions, application of high pressures modifies the functionality of protein and polysaccharide molecules and significantly promotes the emulsifying activities. Application of high pressures also modulates the emulsion microstructure without any destabilization and gelation of protein molecules. The lipid oxidation in HPP-treated emulsions can be accelerated, particularly with higher pressure levels, while the HPP utilization on emulsions in acidic conditions can highly inhibit the growth of spoilage and pathogenic microorganisms. In this study, the effects of HPP on the physicochemical, rheological and antimicrobial properties of emulsion-based delivery systems are reviewed. Physicochemical mechanisms dominant over the destabilization of emulsion systems and knowledge gaps related to the practical exploitations of HPP in the design and manufacture of food-grade colloidal delivery systems are also addressed. Graphical abstract: Image 1 Highlights: HPP treatment changes the physical stability and rheology of food-grade emulsions. HPP treatment improves the emulsion viscoelasticity and particles homogeneity. Application of HPP at pressures >400 MPa decreases the emulsifying activity index. HPP treated emulsions are more prone to lipid oxidation.